2014
DOI: 10.11138/fneur/2014.29.1.057
|View full text |Cite
|
Sign up to set email alerts
|

Elman neural network for the early identification of cognitive impairment in Alzheimer�s disease

Abstract: Early detection of dementia can be useful to delay progression of the disease and to raise awareness of the condition. Alterations in temporal and spatial EEG markers have been found in patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI). Herein, we propose an automatic recognition method of cognitive impairment evaluation based on EEG analysis using an artificial neural network (ANN) combined with a genetic algorithm (GA). The EEGs of 43 AD and MCI patients (aged between 62 and 88 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Similar to previous studies which demonstrated the utility of machine learning models for predicting outcomes closely related to the risk of disability in the older people as fall risk [33,34] or dementia [35,36], these results demonstrate a fairly high level of accuracy (exceeding 80% case classification accuracy) for predicting functional status one year ahead using individual features and information available from a standardized CGA which are available, for example, at the time of admission to rehabilitation program. The performance of models generated by SVMs exceeded the performance of models analysed using LR model constrained by the same independent variables.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to previous studies which demonstrated the utility of machine learning models for predicting outcomes closely related to the risk of disability in the older people as fall risk [33,34] or dementia [35,36], these results demonstrate a fairly high level of accuracy (exceeding 80% case classification accuracy) for predicting functional status one year ahead using individual features and information available from a standardized CGA which are available, for example, at the time of admission to rehabilitation program. The performance of models generated by SVMs exceeded the performance of models analysed using LR model constrained by the same independent variables.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies explored several EEG features for AD and MCI discrimination from HC, focusing on binary discrimination problems (AD vs. HC, MCI vs. HC and AD vs. MCI) [ 16 , 17 , 18 , 19 , 20 ]. To the best of our knowledge, only one study performed a three-way classification, although via binary classifiers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study had multiple positive aspects, including extensive clinical and neuropsychological profiling of participants, matched groups (for age, sex and education) and a good sample size relative to earlier studies (e.g. Ahmadlou, Adeli, & Adeli, 2010;Bertè, Lamponi, Calabrò, & Bramanti, 2014;Kashefpoor, Rabbani, Barekatain, 2016;McBride et al, 2015;Musaeus et al, 2018). Additionally, our MCI group included only participants with amnestic MCI sub-type, which is more closely linked with AD than non-amnestic MCI (Csukly et al, 2016).…”
Section: Discussionmentioning
confidence: 99%